Need Help?

  • Notes
  • Comments & Questions

Find \(\int \frac{x}{\sqrt{x^{2}+4}} d x\)

\(\sqrt{x^{2}+a^{2}}\)

\(x=2 \tan \theta\)

let \(u=x^{2}+4\)

\(d u=2 x d x\)

\(\int \frac{x}{\sqrt{u}} d x=\int \frac{x}{\sqrt{u}} \frac{2}{2} d x\)

\(=\frac{1}{2} \int \frac{2 x}{\sqrt{u}} d x=\frac{1}{2} \int \frac{d u}{\sqrt{u}}\)

\(=\frac{1}{2} \int \frac{d u}{u^{\frac{1}{2}}}=\frac{1}{2} \int u^{-\frac{1}{2}} d u=\frac{1}{2}\left[2 u^{\frac{1}{2}}\right]+c\)

\(=u^{\frac{1}{2}}+c\)

\(\int \frac{x}{\sqrt{x^{2}+4}} d x=u^{\frac{1}{2}}+c\)

\(=\left(x^{2}+u\right)^{\frac{1}{2}}+c=\sqrt{x^{2}+u}+c\)

Find \(\int_{0}^{\frac{3 \sqrt{3}}{2}} \frac{x^{3}}{\left(4 x^{2}+9\right)^{3 / 2}} d x\)

\(\left(4 x^{2}+9\right)^{3 / 2}=\sqrt{\left(4 x^{2}+9\right)}^{3}\)

\(\sqrt{x^{2}+a^{2}} \rightarrow x=a \tan \theta\)

let \(u=2 x \rightarrow d{u}=2 d x \rightarrow d x=\frac{d u}{2}\)

\(u=2 x \rightarrow x=\frac{u}{2}\)

when \(x=0 \quad \rightarrow u=0\)

when \(x=\frac{3 \sqrt{3}}{2} \rightarrow u=3 \sqrt{3}\)

\(u=2 x \rightarrow u^{2}=u x^{2}\)

\(I=\int_{0}^{\frac{3 \sqrt{3}}{2}} \frac{x^{3}}{\left(\sqrt{4 x^{2}+9}\right)^{3}} \cdot d x=\int_{0}^{3 \sqrt{3}} \frac{\left(\frac{u}{2}\right)^{3}}{\left(\sqrt{u^{2}+9}\right)^{3}} \cdot d x\)

\(=\int_{0}^{3 \sqrt{3}} \frac{\frac{u^{3}}{8}}{\left(\sqrt{u^{2}+9}\right)^{3}} \cdot \frac{d u}{2}\)

\(I=\frac{1}{16} \int_{0}^{3 \sqrt{3}} \frac{u^{3}}{(\sqrt {u^{2}+9})^{3}} \cdot d u\)

let \(u=3 \tan \theta \rightarrow d u=3 \sec ^{2} \theta d \theta, \quad \frac{-\pi}{2} \le \theta \le \frac{\pi}{2}\)

\(\sqrt{u^{2}+9}=3 \sec \theta\)

when \(u={0} \rightarrow \tan \theta =0 \rightarrow \theta =\tan ^{-1}(0)=0\)

when \(u=3 \sqrt{3} \rightarrow \tan \theta=\frac{u}{3}=\frac{3 \sqrt{3}}{3}=\sqrt{3} \:, \theta = \tan^{-1} ({\sqrt 3})\)

\(=\frac{\pi}{3}\)

\(I = {\frac{1}{16}} \int_{0}^{3\sqrt 3} \frac{u^{3}}{\left(\sqrt{u^{2}+9}\right)^{3}} \cdot d u\)

\(0, \frac{\pi}{3}, \quad u=3 \tan \theta, \sqrt{u^{2}+9}=3 \sec \theta\)

\(d u=3 \sec ^{2} \theta d \theta\)

\(I=\frac{1}{16} \int_{0}^{\frac{\pi}{3}} \frac{(3 \tan \theta)^{3}}{(3 \sec \theta)^{3}} \cdot 3 \sec ^{2} \theta d \theta\)

\(=\frac{1}{16} \int_{0}^{\frac{\pi}{3}} \frac{9 \tan ^{3} \theta}{9 \sec ^{3} \theta} \cdot 3 \sec ^{2} \theta d \theta\)

\(I=\frac{3}{16} \int_{0}^{\frac{\pi}{3}} \frac{\tan ^{3} \theta}{\sec ^{3} \theta} \cdot \sec ^{2} \theta d \theta\)

\(=\frac{3}{16} \int_{0}^{\frac{\pi}{3}} \frac{\tan ^{3} \theta}{\sec \theta} \cdot d \theta\)

\(= \frac{3}{16} \int_{0}^{\frac{\pi}{3}} \frac{\tan ^{2} \theta}{\sec \theta} \cdot \tan \theta \cdot \frac{\sec \theta}{\sec \theta} \cdot d \theta\)

but I have \(\tan ^{2} \theta=\sec ^{2} \theta-1\)

\(I=\frac{3}{16} \int_{0}^{\frac{\pi}{3}} \frac{\left(\sec ^{2} \theta-1\right)}{\sec ^{2} \theta} \cdot \tan \theta \cdot \sec \theta \cdot d \theta\)

let \(t=\sec \theta \rightarrow d t=\sec \theta \tan \theta d \theta\)

when \(\theta=0 \quad \rightarrow t=\sec (0)=1\)

when \(\theta=\frac{\pi}{3} \rightarrow t=\sec \left(\frac{\pi}{3}\right)=2\)

\(I=\frac{3}{16} \int_{1}^{2} \frac{\left(t^{2}-1\right)}{t^{2}} \cdot d t\)

\(=\frac{3}{16} \int_{1}^{2}\left(\frac{t^{2}}{t^{2}}-\frac{1}{t^{2}}\right) d t\)

\(=\frac{3}{16} \int_{1}^{2} 1-t^{-2} d t=\frac{3}{16}\left[t+\frac{1}{t}\right]_{1}^{2}\)

\(=\frac{3}{16}\left[2+\frac{1}{2}-\left(1+\frac{1}{1}\right)\right]\)

\(=\frac{3}{16}\left[2+\frac{1}{2}-1-1\right]=\frac{3}{16}\left[\frac{1}{2}\right]=\frac{3}{32}\)

\(I = \int_{0}^{\frac{3 \sqrt{3}}{2}} \frac{x^{3}}{\left(\sqrt{\left(4 x^{2}+9\right)}\right)^{3 / 2}} d x=\frac{3}{32}\)

No comments yet

Join the conversation

Join Notatee Today!